New data on morphology and distribution of Alona werestschagini Sinev, 1999—the only Arcto-Alpine species of Chydoridae (Cladocera: Anomopoda) known to date - Sinev, Artem Y.; Garibian, Petr G.; Kirova Nadezhda А.; Neplyukhina, Alisa A. (Zootaxa, 2021)
Detailed study of morphology of Alona werestschagini Sinev, 1999 (Crustacea: Cladocera) confirms its affinities with Alona guttata Sars, 1862. A. werestschagini is the only Arcto-Alpine species among the family Chydoridae, distributed along Arctic coast of Eurasia and in mountains of Central Asia, newer recorded in temperate lowlands of the continent. In our opinion, the species evolved in mountainous regions of Central Asia, while its spreading to Arctic regions took place in Pleistocene.